Respuesta :
Answer:
x = -36
Step-by-step explanation:
Subtract 9 from 3.2(x−6)=14⋅−6
Multiply 14 by −6.2(x−6)=−84
Divide each term
Simplify the left side.
Move all terms not containing x to the right side of the equation.
x = -42 + 6
Add -42 & 6
x = -36
Let’s rewrite the equation first:
2(x - 6) = 14(3 - 9)
Let’s solve this through steps. The first step is to distribute:
2x - 12 = 42 - 126
Now, let’s add 12 to both sides:
2x - 12 + 12 = 42 - 126 + 12
2x = 42 - 114
Now, let’s divide 2 from both sides:
2x / 2 = (42 / 2) - (114 / 2)
x = 21 - 57
21 - 57 = -36
x = -36
2(x - 6) = 14(3 - 9)
Let’s solve this through steps. The first step is to distribute:
2x - 12 = 42 - 126
Now, let’s add 12 to both sides:
2x - 12 + 12 = 42 - 126 + 12
2x = 42 - 114
Now, let’s divide 2 from both sides:
2x / 2 = (42 / 2) - (114 / 2)
x = 21 - 57
21 - 57 = -36
x = -36